Memory Specificity and Mindfulness Jointly Moderate the Effect of Reflective Pondering on Depressive Symptoms in Individuals With a History of Recurrent Depression - Brennan, Kate (J Abnorm Psychol, 2015)
In previously depressed individuals, reflective thinking may easily get derailed and lead to detrimental effects. This study investigated the conditions in which such thinking is, or is not, adaptive. Levels of mindfulness and autobiographical memory specificity were assessed as potential moderators of the relationship between reflective thinking and depressive symptoms. Two hundred seventy-four individuals with a history of three or more previous episodes of depression completed self-report measures of depressive symptoms, rumination—including subscales for reflection and brooding—and mindfulness, as well as an autobiographical memory task to assess memory specificity. In those low in both mindfulness and memory specificity, higher levels of reflection were related to more depressive symptoms, whereas in all other groups higher levels of reflection were related to fewer depressive symptoms. The results demonstrate that the relation between reflective pondering and depressive symptoms varies depending on individual state or trait factors. In previously depressed individuals, the cognitive problem-solving aspect of reflection may be easily hampered when tendencies toward unspecific processing are increased, and awareness of mental processes such as self-judgment and reactivity is decreased.